Controls on fluvial meander‐belt thickness and sand distribution: Insights from forward stratigraphic modelling. Issue 5 (6th January 2021) - Yan, Na; Colombera, Luca; Mountney, Nigel P.
Abstract: Fluvial point‐bar evolution commonly involves multiple stages of bar development driven by changes in the style of meander transformations. Complicated planform morphologies are widely recognized in remote‐sensing imagery, but the relationships between meander‐bend evolutionary behaviour and stratigraphic architecture, facies distribution, and sand volumes remain poorly understood. This study applies a geometric forward stratigraphic model (Point‐Bar Sedimentary Architecture Numerical Deduction – 'PB‐SAND') to simulate the internal sedimentary architecture of 24 meander‐belt segments that evolved via a broad range of meander‐bend transformation styles. Modelling inputs are constrained by channel trajectories inferred from high‐resolution Light Detection and Ranging (LiDAR) datasets, lithological information from a sedimentological database (Fluvial Architecture Knowledge Transfer System – 'FAKTS') and geological knowledge of trends in point‐bar lithology (for example, decrease in sand proportion with sinuosity, downstream of bend apices, and beyond the transition from point‐bar to counter‐point‐bar deposits) and in channel bathymetry (depth variations across pools and riffles). Modelling results are used to explore how the relative distribution of sand and mud is controlled by the styles of point‐bar transformation, quantified by the relative degree of meander translation versus expansion, and by the amount of bend rotation. The 24 models are classified into three groups based on cluster analysis of their mean migration angle, mean apex rotation, mean sinuosity, standard deviation of channel circular variance and preservation ratio; these quantities are known to be controlled by meander transformation types. Quantitative comparisons across these groups and relationships between metrics of planform change and quantifications of point‐bar deposits demonstrate how meander planform evolution controls point‐bar thickness and sand volume. Locally, the thickness of sand in bar deposits is controlled by the interplay of facies trends and spatial variations in bar thickness that reflect bathymetric changes, both related to local hydrodynamics. The proposed workflow establishes linkages between planform morphologies and three‐dimensional facies distributions; it can be employed to characterize the distribution of subsurface porous volumes where the planform history of meander bends can be reconstructed.